Differences in the bodyweight, hydration levels, lean mass, and fat mass in Spanish junior elite judokas - Gamero-del Castillo, D.; Calvo, J. L.; Navandar, A.; López Diaz de Durana, A. (International Journal of Environmental Research and Public Health, 2020)
Combat sports have a great interest in society and among professional sports. They are an important group of sports in the Olympic Games, but the strategies carried out by athletes to reduce body weight for weighing day, is famously known, suffering the adverse physical and psychological effects of rapid weight loss. This could compromise not only the performance, but the health and development of young athletes. A total of 22 elite male judokas (18.05 ± 1.05 years old) were evaluated during four different competitions in one season; the variables of body weight, water levels, and lean and fat mass were measured by bioimpedance (BIA), (Tanita BC545N) during one season. Using the linear mixed model test, we found significant differences in bodyweight variable during the competitions 3-4. The water level variable showed significant differences in all competitions, except for 2-4. Body mass index was significantly different in all competitions, being higher in the later competitions, except between competitions 1-2 and 2-3. Judokas participate in weight loss methods for their weigh-in days. Furthermore, the age at which the athletes reduced their water levels are worrisome. These results could be used to create healthy programs, especially in elite judokas, in order to carry out strategies before, during, and after competitions with weight loss and controlled water levels increasing future performance and health.